Comparative study on the susceptibility of different laboratory strains of Glossina species to Trypanosoma simiae - Moloo, S.K.; Zweygarth, E.; Sabwa, C.L. (Wiley, 1994)
Abstract. Teneral tsetse of four Glossina species from laboratory‐reared colonies were fed on four Large White pigs infected with three different stocks of Trypanosoma simiae isolated in Coast Province, Kenya. Thereafter the tsetse were maintained on goats and dissected on day 28 to determine the trypanosome infection rates. Glossina brevipalpis was as susceptible as G.pallidipes whilst G.palpalis gambiensis was not susceptible to T.simiae CP 11 a stock causing acute infection, which was isolated from a wild G.austeni. Glossina brevipalpis was as susceptible as G.pallidipes to another stock causing acute infection, T.simiae CP 813 isolated from a wild G.pallidipes. Glossina morsitans centralis was also as susceptible as G.brevipalpis and G.pallidipes whilst G.p.gambiensis was not susceptible to this T.simiae stock. Glossina m.centralis showed very low susceptibility to a stock causing chronic infection, T.simiae CP 1896 isolated from a bushpig, whilst G.brevipalpis, G.p.gambiensis and G.pallidipes could not be infected by this T.simiae stock. Male Glossina were generally more susceptible than females to the three T.simiae stocks.